Empathy in game design - Exploring a human-centric approach in designing engaging video game experiences - Xinyi Tan; Chin Ike Tan (Pejabat Karang Mengarang UPSI, 2022)
The link between engagement and player emotions has been extensively explored by researchers in recent years. Empathy, which is the innate ability to accurately perceive another person's current feelings and meanings can be broadly categorized into two main human-centric design approaches - cognitive empathy and affective empathy. Certain forms of media especially time-based media have been proven to better exploit viewers' empathy and provide a more engaging experience when a human-centric design approach is applied. The aim of this research paper is to explore if a human-centric design approach can provide the same level if not more immersive engagement when designing video game experiences. The initial research into a human-centric design approach in video games will be obtained through an exploratory research design involving six tertiary-level students in the field of game design between the ages of 20 to 24 over a period of two weeks. The exploratory research encompassing of a semi-structured interview process with eight key questions relating to the respondent's experience with empathy in games determined the advantages of planning and designing a game using a human-centric game design approach. The research determined that human-centric game design focusing on affective empathy provides a high possibility of a more engaging game experience that is strengthened by in-game narrative elements resulting in increased time spent in-game. This can be attributed to two main factors - firstly, a stronger player connection through direct empathy to their virtual avatars or in-game characters, regardless of the player's moral standings and principles. Secondly, an immersive narrative structure produces a deeper player attachment toward game characters and game worlds.